Tradisi Nazam sebagai Identitas Sastra Pesantren: Studi Pada Pondok Pesantren Mahasiswa Fatimah Al-Batul Pekalongan - Muhammad Khoiruzzabidi; Nur Fatikhatul Jannah; Rachma Ismatul Maula; Zahra Aulia; Nailatul Mafazah; Abdul Mukhlis (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2026)
This research investigates the significance of the nazam (rhythmic poetry) tradition as a distinctive literary characteristic of the Fatimah Al-Batul Student Islamic Boarding School in Pekalongan, and explores the strategies used by the school to maintain its appeal in the digital era. Pesantren literature, combining religious values, local culture, and Islamic knowledge often featuring moral and Sufistic teachings is crucial. Here, Nadhom serves as the primary pedagogical tool for memorizing and comprehending religious texts like tauhid and Arabic grammar. Utilizing a qualitative descriptive method with a functional discourse analysis approach, data was collected through non participant observation and in-depth interviews with a kyai and four selected informants, focusing on the routine practice of lalaran (collective rhythmic recitation) of classical books. The findings demonstrate that nazam is vital, not only making memorization easier and more enjoyable but also establishing a unique cultural identity for the pesantren. To counter the challenge of students finding classical nazam language difficult, the pesantren employs strategies that include teaching it using everyday language, especially Jawa Pegon, and linking it to contemporary issues; integrating it into art by accompanying it with rebana or local songs during events; and leveraging social media for content, quotes, and documentation. These efforts successfully ensure that Islamic teachings are perceived as beautiful and dynamic, preserving the tradition within the students spiritua llives.